2018
DOI: 10.3390/su10020347
|View full text |Cite
|
Sign up to set email alerts
|

To License or Not to License Remanufacturing Business?

Abstract: Many original equipment manufacturers (OEMs) face the choice of whether to license an independent remanufacturer (IR) to remanufacture their used products. In this paper, we develop closed-loop supply chain models with licensed and unlicensed remanufacturing operations to analyze the competition and cooperation between an OEM and an IR. The OEM sells new products and collects used products through trade-ins, while the IR intercepts the OEM's cores to produce remanufactured products and sell them in the same ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
(46 reference statements)
0
19
0
Order By: Relevance
“…The technology licensing remanufacturing has received extensive attention in the recent operational management literature (e.g., Zou et al [3], Huang and Wang [5], Hong et al [7], Huang and Wang [8], Ma et al [9], Hashiguchi [13], Oraiopoulos et al [14], Abdulrahman et al [15], and Niu and Zou [16]). In particular, Hashiguchi [13] summarized cases in Japan and USA of conflicts in third-party remanufacturing between TPRs and manufacturers, and suggested that TPRs should purchase licenses from manufacturers so as to avoid such conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The technology licensing remanufacturing has received extensive attention in the recent operational management literature (e.g., Zou et al [3], Huang and Wang [5], Hong et al [7], Huang and Wang [8], Ma et al [9], Hashiguchi [13], Oraiopoulos et al [14], Abdulrahman et al [15], and Niu and Zou [16]). In particular, Hashiguchi [13] summarized cases in Japan and USA of conflicts in third-party remanufacturing between TPRs and manufacturers, and suggested that TPRs should purchase licenses from manufacturers so as to avoid such conflicts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Cat Reman provides remanufacturing services for many major manufacturers, such as Perkins, Alcoa, Ford, and Honeywell. Xin Meifu, the largest automobile gearbox remanufacturer in China, acts as a remanufacturing service provider for ZF Friedrichshafen AG and Aisin, the two largest gearbox manufacturers in the world [9]. For more examples of the licensing remanufacturing see the list in Table 1, which implies that licensing remanufacturing is an important form of remanufacturing in China [10].…”
Section: Introductionmentioning
confidence: 99%
“…Shen, et al [24] analyzed two main formats deployed by the original manufacturer, who chooses either self-recovery and self-remanufacturing or authorization remanufacturing, with license fees charged from the authorized distributors. Most recently, Ma, et al [25] compared unlicensed remanufacturing and licensed remanufacturing strategies with the original manufacturer and independent remanufacturer, and developed three models to demonstrate cooperation and coordination between the remanufacturing undertakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Assumption 4. Both newly and secondary-made products are traded in the same market, the whole quantity of which equals consumption demand Q [25,37]. Assumption 5.…”
Section: Model Assumptionsmentioning
confidence: 99%
“…Lin and Chen [2] propose a "3PSP" solution, where a 3PSP, as an authorized service provider (ASP), not only processes the returned defectives, but also orders new service parts to fulfill the turnaround time [19]. Ma et al [20] find that it is beneficial for an OEM to license ASPs to remanufacture, while Yan et al [21] suggest that OEMs conducting take-back operations can improve the overall remanufacture operations. Usually, a 3PSP would order new service parts from ODMs according to the rolling plan from OEMs.…”
Section: Introductionmentioning
confidence: 99%